2022
DOI: 10.3390/brainsci12091126
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Progressive Supranuclear Palsy: Real World Data from the Second Largest Health Plan in Israel

Abstract: Progressive supranuclear palsy (PSP) is a rare and fatal neurodegenerative movement disorder and no disease modifying therapy (DMT) is currently available. This study aims to assess the epidemiology of PSP in Israel and to describe its clinical features. This retrospective analysis identified patients with PSP between 2000 and 2018 over the age of 40 years at first diagnosis (index date). We identified 209 patients with ≥1 diagnosis of PSP. Of those, 88 patients satisfied the inclusion criteria with a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In addition, these findings are in line with those of resembling conditions; AD [31] and PD [27,32,33]. The higher costs during the year prior index can be explained by the known delayed in PSP's diagnosis [4], and by higher HCRU leads to the diagnosis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, these findings are in line with those of resembling conditions; AD [31] and PD [27,32,33]. The higher costs during the year prior index can be explained by the known delayed in PSP's diagnosis [4], and by higher HCRU leads to the diagnosis.…”
Section: Discussionsupporting
confidence: 81%
“…Additional limitations are those inherit to database research. First, we identified PwPSP only by one diagnosis, which may cause misclassification of the disease; however, in a previous analysis of PSP's epidemiology, using the same criteria, we showed that our results are in line with the other publications [4]. The consequence of such non-differential misclassification of PSP is dilution of the measure of effect size and underestimation of the true economic burden of the disease due to "bias towards the null".…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…1 PSP characteristics include vertical supranuclear palsy, postural instability with unexplained falls, akinesia and frontal cognitive dysfunction. 2 The pathological features of PSP consist of neuronal loss, globose neurofibrillary tangles, tau-positive inclusion found in tufted astrocytes, and gliosis mainly in the basal ganglia, cerebellum, brainstem, and to a lesser extent, cerebral cortex. [3][4][5] Thus, the definitive diagnosis of PSP requires neuropathological examination.…”
mentioning
confidence: 99%